On the dynamics of the seasonal variation in the South China Sea throughflow transport. Issue 12 (16th December 2013) - Yang, Jiayan; Lin, Xiaopei; Wu, Dexing
Abstract : [1] The Luzon Strait transport (LST) of water mass from the Pacific Ocean to the South China Sea (SCS) varies significantly with seasons. The mechanisms for this large variability are still not well understood. The steady‐state island rule, which is derived from a steady‐state model, is not applicable to seasonal time scale variations in a large basin like the Pacific Ocean. In this paper, we will use a theoretical model that is based on the circulation integral around the Philippines. The model relates the LST variability to changes in the boundary currents along the east coast of the Philippines, including the North Equatorial Current (NEC) Bifurcation Latitude (NECBL), the transports of Kuroshio and Mindanao Currents (KC and MC), and to the local wind‐stress forcing. Our result shows that a northward shift of the NECBL, a weakening of the KC or a strengthening of the MC would enhance the LST into the SCS. This relationship between the LST and the NEC‐KC‐MC is consistent with observations. The analytical result is tested by a set of idealized numerical simulations. Key Points: The seasonal SCSTF transport is forced by WBCs off the Philippines Both WBC transports and bifurcation latitude are important First theoretical explanation for seasonal SCSTF transport